Fiducial markers and spacers in prostate radiotherapy: current applications. (March 2014) - Ng, Michael; Brown, Elizabeth; Williams, Andrew; Chao, Michael; Lawrentschuk, Nathan; Chee, Raphael
Abstract : Objectives: To review the use of fiducial markers and spacers in prostate radiotherapy (RT). Materials and Methods: We reviewed the literature on the use of fiducial markers to improve accuracy in delivery of RT for prostate cancer. We discuss the rationale for fiducials, the types available, the procedures and complications. We also reviewed the current literature on the novel use of spacers to reduce rectal toxicity during prostate irradiation. Results: Prostate motion is a significant problem both during and between RT treatments. Intraprostatic fiducials allow accurate prostate localisation ensuring RT treatment accuracy. Insertion of gold fiducials are a cost‐effective marker that can be easily and quickly implanted and at least three fiducials are recommended. Severe complications from fiducial implantation are uncommon and marker migration is very rarely clinically significant. Spacers are a novel method to distance the rectum from the prostate during RT, reducing acute rectal toxicity, and have no detrimental impact on health‐related quality of life. Conclusions: Intraprostatic fiducials are now standard of care when delivering prostate RT and early data shows benefit of spacers in reducing RT rectal toxicity.